The difference between cystatin C- and creatinine-based eGFR is associated with adverse cardiovascular outcome in patients with chronic kidney disease. (October 2021) - Kim, Hyoungnae; Park, Jung Tak; Lee, Joongyub; Jung, Ji Yong; Lee, Kyu-Beck; Kim, Yeong-Hoon; Yoo, Tae-Hyun; Kang, Shin-Wook; Choi, Kyu Hun; Oh, Kook-Hwan; Ahn, Curie; Han, Seung Hyeok; et al.
Abstract: Background and aims: Decreased kidney function is an important risk factor for cardiovascular disease (CVD). However, assessing risk of CVD may be difficult when there is a gap between creatinine- and cystatin C-based estimated glomerular filtration rate (eGFR). We studied the association of the difference in eGFRs with major adverse cardiovascular events (MACE) in patients with chronic kidney disease (CKD). Methods: This prospective cohort study was conducted in 2076 patients with CKD stages based on the KDIGO guideline (eGFR categories of G1: ≥90; G 2: 60–89; G3: 30–59; G4: 15–29; G5: <15 mL/min/1.73 m 2 without kidney replacement therapy). The difference in eGFR (eGFRdiff ) was calculated by subtracting the cystatin C-based eGFR (eGFRcys ) from the creatinine-based eGFR (eGFRcreat ). The primary outcome was MACE, defined as non-fatal acute myocardial infarction and unstable angina, stroke, congestive heart failure, symptomatic arrhythmia, and cardiac death. Results: During a median follow-up of 4.1 years, MACE occurred in 147 patients (incidence rate, 15.0 per 1000 patient-years). When patients were categorized into baseline eGFRdiff tertiles, the highest tertile was associated with a significantly higher risk of MACE (hazard ratio, 2.12; 95% confidence interval [CI], 1.28–3.51) than the lowest tertile when adjusted for eGFRcreat, eGFRcys, or eGFR based on both creatinine and cystatin C. Patients in the highest tertile had more baseline coronary artery calcification (CAC) than those in the lowest tertile (odds ratio [OR], 1.38; 95% CI, 1.03–1.86). In addition, 978 patients had data for both baseline and follow-up CAC at year 4. In this subgroup, baseline eGFRdiff was significantly associated with accelerated CAC progression (≥50/year) (OR, 1.03; 95% CI, 1.01–1.05). Conclusions: A large positive difference between eGFRcreat and eGFRcys was associated with a higher risk of MACE and faster CAC progression in patients with CKD. Therefore, careful monitoring of CVD is needed for patients with a higher eGFRdiff . Graphical abstract: Image 1 Highlights: Cardiovascular disease is a leading cause of death in patients with chronic kidney disease. Assessing risk of cardiovascular disease may be difficult when there is a gap between creatinine- and cystatin C-based eGFR. Risk of major adverse cardiovascular events was high in patients with high eGFR difference between creatinine and cystatin C. Patients with high eGFR difference also had high risk of coronary artery calcification progression.